2020
DOI: 10.3390/met10010069
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography Measurement of Mirror-Finished Surfaces Using Fringe-Patterned Illumination

Abstract: Mirror-finished surface products have a wide range of applications in different engineering industries, such as power generation, aerospace, semiconductors and optics. The surface topography of mirror-finished products is typically measured in a metrology laboratory, which is typically time consuming and cannot be integrated into the manufacturing process. To allow for in-situ product quality assurance and automatic tool change for manufacturing processes, a more accurate and responsive surface-measurement met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Laser confocal microscopy (VK-X2000, Keyence Ltd., Japan) was adopted to observe the surface topographies of UHMWPE samples before and after the wear tests. Meanwhile, the volume loss and the surface roughness ( S q ) after the wear tests were investigated (Fu et al , 2020; Paweł et al , 2020). Based on the volume loss, the wear rate was calculated according to equations (1).…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Laser confocal microscopy (VK-X2000, Keyence Ltd., Japan) was adopted to observe the surface topographies of UHMWPE samples before and after the wear tests. Meanwhile, the volume loss and the surface roughness ( S q ) after the wear tests were investigated (Fu et al , 2020; Paweł et al , 2020). Based on the volume loss, the wear rate was calculated according to equations (1).…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…For example, surface topography measurement in mirror-finished products can be time-consuming and difficult to integrate into manufacturing processes. Study [6] reports the use of sub-micron surface fluctuation in combination with light-scattering effects and image processing to perform surface texture analysis. A non-contact surface inspection system using a fringe-patterned illumination method is proposed.…”
Section: Surface Metrologymentioning
confidence: 99%
“…Tensile, flexural, hardness, and impact tests were performed and it was found that the hybrid composites had better properties than pure aluminium. Ceramic materials (CMCs), which are used in very high temperature settings, use a ceramic as the matrix and strengthen it with short fibres, or hairs along with silicon carbide and boron nitride [12]. The usage of waste products originating from agricultural operations (red clay, fly ash) and agro-based materials (rice husk ash, bamboo leaf ash, ground nut shell ash, among others) is increasingly improving aluminium matrix composite (AMC).…”
Section: Introductionmentioning
confidence: 99%